The Spatial Distribution of Petroleum Hydrocarbon Contamination in Groundwater Around Fuel Storage Tank - Utami, Ayu; Sahetapi, Calvin Alex; Rahayu, Mey Yani Puji; Kristanto, Wisnu Aji Dwi; Raharjo, Wiji; Isnaini, RR Desi Kumala; Fahri, Ricky Al; Anifah, Eka Masrifatus (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Groundwater is vital for domestic, agricultural, and industrial use; however, previous studies have indicated that its quality often fails to meet drinking water standards. The sources of groundwater contaminants can be from domestic, industrial, saltwater intrusion, surface waste ponds, pipelines, mine pits, underground storage tanks, waste pits, etc. This research investigates the spatial distribution of Total Petroleum Hydrocarbons (TPH) contamination in groundwater surrounding fuel storage tanks, using the LeGrand method to assess groundwater vulnerability based on five physical environmental parameters. The study employs a quantitative approach, incorporating primary data from well measurements and secondary data from geological and land use maps. The results reveal that shallow groundwater levels significantly increase vulnerability to contamination, while the type of soil and aquifer permeability also play critical roles in contaminant transport dynamics. In the second research location, the analysis focuses on benzene contamination, with low concentrations below 0.02 ppb. Despite the low levels detected, the potential for contamination remains a concern due to the proximity of the gas station to residential areas. Statistical correlation analysis demonstrates a significant inverse relationship between TPH concentrations and vulnerability scores. The study underscores the importance of preventive measures to mitigate contamination risks, involving collaboration among stakeholders.